A highly-efficient palladium-catalyzed aminocarbonylation/SNAr approach to dibenzoxazepinones1. Issue 5 (12th May 2015) - Shen, Chaoren; Neumann, Helfried; Wu, Xiao-Feng
<x xml:space="preserve">Abstract</x> A practical protocol for the synthesis of dibenzo[b, e][1, 4]oxazepin-11(5H)-ones has been developed. By virtue of Pd-catalyzed aminocarbonylation and aromatic nucleophilic substitution, 61 examples of the desired dibenzoxazepinones were obtained in moderate to excellent isolated yields (54–92%).